THE EMOTIONAL STABILITY OF THE CHILD’S DEVELOPMENT IN THE TRANSITION PERIOD DURING ADOLESCENCE IS BASED ON THE ISLAMIC-EDUCATION PSYCHOLOGICAL VIEWS - Oqy Andaresta (Edusoshum : Journal of Islamic Education and Social Humanities, 2022)
Many children are started to grow into teenagers, but child’s emotional stability is still unstable due to several internal and external factors. Emotional stability affects the quality of learning to which a child is about to grow into a teenager. This research aims to solve the emotional ability of child development during the teenager transition period. This research design is qualitative research focused on a systematic literature review by examining scientific articles and manuscripts from the literature that are relevant to the problems raised in this research. The data sources are divided into two kinds, primary and secondary sources. The primary data are books used as main sources concerning the study of child development during Adolescence. Meanwhile, the secondary data are scientific research considered relevant to this study. The analysis method is descriptive analysis to determine the emotional stability of the child’s development during teenager transition in the Islamic views. The research result shows that intervention from parents and teachers in the stability and the process during transition periods is needed to improve the quality of a child’s learning. The intervention of the emotional stability in children during this transition period with a humanistic approach.] [Banyak anak yang mulai tumbuh menjadi remaja, namun kestabilan emosi anak masih labil karena beberapa faktor internal dan eksternal. Kestabilan emosi mempengaruhi kualitas pembelajaran yang akan dilakukan seorang anak untuk tumbuh menjadi remaja. Penelitian ini bertujuan untuk mengetahui perkembangan kemampuan emosional anak pada masa transisi remaja. Desain penelitian ini adalah penelitian kualitatif yang berfokus pada tinjauan pustaka yang sistematis dengan menelaah artikel ilmiah dan manuskrip dari literatur yang relevan dengan masalah yang diangkat dalam penelitian ini. Sumber data dibedakan menjadi dua macam, yaitu sumber primer dan sumber sekunder. Data primer berupa buku-buku yang digunakan sebagai sumber utama mengenai kajian perkembangan anak pada masa remaja. Sedangkan data sekunder adalah penelitian ilmiah yang dianggap relevan dengan penelitian ini. Metode analisis yang digunakan adalah analisis deskriptif untuk mengetahui kestabilan emosi perkembangan anak pada masa transisi remaja dalam pandangan Islam. Hasil penelitian menunjukkan bahwa intervensi dari orang tua dan guru dalam stabilitas dan proses selama masa transisi diperlukan untuk meningkatkan kualitas belajar anak. Intervensi kestabilan emosi pada anak pada masa transisi ini dengan pendekatan humanistik.